2018
DOI: 10.1186/s12887-018-1009-y
|View full text |Cite
|
Sign up to set email alerts
|

The relationship of undernutrition/psychosocial factors and developmental outcomes of children in extreme poverty in Ethiopia

Abstract: BackgroundExtreme poverty is severe deprivation of basic needs and services. Children living in extreme poverty may lack adequate parental care and face increased developmental and health risks. However, there is a paucity of literature on the combined influences of undernutrition and psychosocial factors (such as limited play materials, playground, playtime, interactions of children with their peers and mother-child interaction) on children’s developmental outcomes. The main objective of this study was, there… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
40
0
5

Year Published

2019
2019
2024
2024

Publication Types

Select...
8
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 41 publications
(45 citation statements)
references
References 44 publications
0
40
0
5
Order By: Relevance
“…Their babies have lower ponderal index and smaller head circumference and are more exposed to pollutants in utero and will probably grow up in a less intellectually stimulating home environment. These are all factors known to negatively impact children’s cognitive development [ 30 , 31 , 32 , 33 ].…”
Section: Discussionmentioning
confidence: 99%
“…Their babies have lower ponderal index and smaller head circumference and are more exposed to pollutants in utero and will probably grow up in a less intellectually stimulating home environment. These are all factors known to negatively impact children’s cognitive development [ 30 , 31 , 32 , 33 ].…”
Section: Discussionmentioning
confidence: 99%
“…Whether WHZ-or MUAC-based criteria are more suitable for identifying children in need of treatment is still under debate Grellety & Golden, 2018;Hossain et al, 2017;Tadesse, Tadesse, Berhane, & Ekström, 2017), but children falling under each of the categories have not yet been well characterised, including with regard to their motor and language development. The association of linear and ponderal growth with child development has been reported from several low-and middle-income settings (Adair et al, 2013;Prado et al, 2017;Worku et al, 2018). However, even in individuals with similar anthropometry, body composition may differ considerably (Deurenberg, Yap, & van Staveren, 1998), and children who are acutely malnourished may be at different risk of developmental delay depending on whether relatively more lean or fat mass has been lost.…”
Section: Introductionmentioning
confidence: 99%
“…In our study, we found that gender had no impact on the quality of care, and girls got equal opportunities to learn, play and develop. Researchers have revealed that poverty is associated with a mass of health problems of children, parental stress and strains in parent–child relationships [18–20]. For example, extreme poverty was strongly linked to restricted learning opportunities and inadequate stimulation at home [17].…”
Section: Discussionmentioning
confidence: 99%